A Study of Storage Related Changes and Effect of Refrigeration on Hematological Parameters and Blood Cell Morphology in EDTA Anticoagulated Blood - Basu, Debdatta; Veluru, Harsha (Annals of Pathology and Laboratory Medicine, 2019)
Introduction: Delayed sample analysis result in changes in measured parameters and morphology of cells, leading to erroneous reports of complete blood counts and peripheral smear reporting. The present study was aimed at evaluating the changes in blood cell counts and morphology on storage, particularly in the local setting and temperature of a tropical country. Materials & Methods: 190 patients referred to the laboratory for complete blood counts and peripheral smear examinations were included in the study. Blood counts and peripheral smear examination was done at 0, 2, 6, and 24 hours. The 6 and 24 hour samples were further studied under three different temperatures, refrigerated, ambient room temperature and at 370C. Statistical difference between values of studied parameter at different time interval was tested using paired t-test. P < 0.05 was considered for statistical significance. Results: There was no significant difference between 0 hour& 2 hour samples in any of the parameters. However a significant change was noted in the platelet count between 6 hour refrigerated and 6 hour un-refrigerated. All the red cell parameters and platelet counts and cell morphology were significantly altered at 24 hours in refrigerated and unrefrigerated samples. Conclusions: Storage of EDTA blood causes changes in the counts and morphology of the cells. Within 2 hours no changes are expected, however if there is an anticipated delay beyond 2 hours, it is worthwhile to refrigerate the samples up to 6 hours, especially when platelet counts are desired.